Exploring the Existence of Innovative Work Behavior among Government Employees in Meruya Selatan Sub-District - Paijan; Hudaya, Agung; Syaifudin; Sugiharjo, Joko (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the influence of transformational leadership and organizational justice on innovative work behavior, with work engagement as an intervening variable. The background of this research is based on the increasing demand for innovation in organizations, which requires leadership that inspires change and a fair organizational climate that fosters employee engagement and proactive behavior. The approach used is quantitative, with data collected through questionnaires distributed to 40 respondents selected using a saturated sampling technique. Data analysis was conducted using Structural Equation Modeling - Partial Least Square (SEM-PLS) with the SmartPLS 4.0 software.The results of the study indicate that: (1) transformational leadership has a positive and significant effect on work engagement; (2) organizational justice has a positive and significant effect on work engagement; (3) transformational leadership has a positive and significant effect on innovative work behavior; (4) organizational justice has a positive and significant effect on innovative work behavior; (5) work engagement has a positive and significant effect on innovative work behavior; (6) transformational leadership has a positive and significant effect on innovative work behavior through work engagement; (7) organizational justice has a positive and significant effect on innovative work behavior through work engagement. These findings highlight the essential role of transformational leadership and organizational justice in fostering employee engagement, which in turn enhances innovative work behavior within the organization.